2019
DOI: 10.1037/spq0000278
|View full text |Cite
|
Sign up to set email alerts
|

Measurement invariance of the Student Risk Screening Scale across time and gender.

Abstract: Universal screening for behavioral/mental health risk is a critical component of multitiered systems of support, allowing for early identification of students in need of prevention and/or intervention services. The Student Risk Screening Scale (SRSS; Drummond, 1994) is one commonly used universal screening tool intended to measure externalizing behavior difficulties. Although the reliability and criterion-related validity of the SRSS has been studied extensively, there are limited data supporting its construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Third, we established invariance of internalizing and externalizing scores over time for students at the elementary, middle, and high school levels. Fredrick et al (2019) indicated a single externalizing factor on the SRSS was invariant for regional elementary student samples across time (fall, winter, spring). Extending their study, our analysis provides the first large-scale examination of measurement invariance for both externalizing and internalizing factors with scores appropriately nested within teachers for students at varying school levels including elementary, middle, and high school.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, we established invariance of internalizing and externalizing scores over time for students at the elementary, middle, and high school levels. Fredrick et al (2019) indicated a single externalizing factor on the SRSS was invariant for regional elementary student samples across time (fall, winter, spring). Extending their study, our analysis provides the first large-scale examination of measurement invariance for both externalizing and internalizing factors with scores appropriately nested within teachers for students at varying school levels including elementary, middle, and high school.…”
Section: Discussionmentioning
confidence: 99%
“…Building on previous SRSS and SRSS-IE inquiry (e.g., Fredrick et al, 2019), in this article we report on factor structure and score reliability of the internalizing and externalizing scales as well as measurement invariance across demographic subgroups and time in a large sample of K–12 U.S. students. Subsequent articles in this programmatic line of inquiry will follow with additional psychometric properties (e.g., predictive validity) informed by IES and NCII Technical Standards.…”
Section: Purposementioning
confidence: 94%
See 2 more Smart Citations
“…Our study highlights a number of challenges present in advancing the use of advanced measurement strategies in education and psychology research. First, large sample sizes are typically needed to conduct IRT, and significant computing power may be necessary for estimating multidimensional models with larger samples (Yao & Boughton, 2007, p. 90) Kamphaus, & Dever, 2015), the SAEBRS (von der Embse et al, 2016) and the SRSS (Fredrick, Drevon, & Jervinsky, 2019). Further, many schools have identified narrow-band mental health issues they wish to target with universal screening efforts, such as district-wide suicide risk screening (Aseltine & DeMartino, 2004;Hallfors et al, 2006), although this is not without controversy (Scherff, Eckert, & Miller, 2005;Fox, Eisenberg, McMorris, Pettingell, & Borowsky, 2013).…”
Section: Multidimensional Irt In Screening Researchmentioning
confidence: 99%